Influence of the Brain-Derived Neurotrophic Factor Gene Polymorphism on Weight Loss Following Intragastric Balloon Intervention: A Cross-Sectional Study - Al-Serri A; Al-Janahi HA; Jamal MH; AlTarrah D; Ziyab AH; Al-Bustan SA (Diabetes, Metabolic Syndrome and Obesity)
Ahmad Al-Serri,1 Hessa A Al-Janahi,1 Mohammad H Jamal,2 Dana AlTarrah,3 Ali H Ziyab,4 Suzanne A Al-Bustan5 1Department of Pathology, Faculty of Medicine, Kuwait University, Kuwait City, Kuwait; 2Department of Surgery, Faculty of Medicine, Kuwait University, Kuwait City, Kuwait; 3Department of Social and Behavioral Science, Faculty of Public Health, Kuwait University, Kuwait City, Kuwait; 4Department of Community Medicine and Behavioral Sciences, Faculty of Medicine, Kuwait University, Kuwait City, Kuwait; 5Department of Biological Sciences, Faculty of Science, Kuwait University, Kuwait City, KuwaitCorrespondence: Ahmad Al-Serri, Human Genetics Unit, Department of Pathology, Faculty of Medicine, Kuwait University, Kuwait, Tel +965 2463 6231, Fax +965 25338905, Email ahmad.alserri@ku.edu.kwBackground and Aim: There is noticeable heterogeneity in weight loss outcomes following intragastric balloon (IGB) treatment, with average weight loss ranging between 11% to 15% of total body weight. Genetic variations associated with obesity have been found to influence weight loss response, however such variations are limited. Therefore, the aim of this study is to investigate the impact of the obesity associated brain-derived neurotrophic factor (BDNF) gene polymorphism rs11030104 with weight loss outcomes following IGB treatment.Methods: In this cross-sectional study, BDNF rs11030104 was analysed in 106 individuals who underwent intragastric balloon treatment. Weight loss metrics were evaluated at the three-month follow-up: percentage of total weight loss (%TWL), percentage of excess weight loss (%EWL), and percentage of body mass index loss (%EBMIL). The effects of additive and dominant genetic models were evaluated. Both linear and logistic regression were applied to assess associations between rs11030104 genotypes and weight loss metrics.Results: A total of 71 participants completed the 3-month follow-up assessment (loss to follow-up: 33%). This study found a significant association between the BDNF rs11030104 polymorphism and weight loss. A-allele carriers showed a better response to IGB treatment. Individuals carrying the AA genotype were found to have a greater %TWL than those carrying the GG genotype at 3 months post-IGB treatment (11.05% vs 5.09%, p=0.003).Conclusion: Our results suggest that BDNF rs11030104 influences the response to weight loss after IGB treatment and therefore could be added to the growing list of genetic variants that predict greater weight loss response.Keywords: BDNF, polymorphism, obesity, intragastric balloon, BMI, weight loss